2000
DOI: 10.1056/nejm200010193431601
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Glyburide and Insulin in Women with Gestational Diabetes Mellitus

Abstract: In women with gestational diabetes, glyburide is a clinically effective alternative to insulin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
426
5
37

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 819 publications
(481 citation statements)
references
References 38 publications
13
426
5
37
Order By: Relevance
“…Glibenclamide has until recently been considered a safe drug to use in pregnancy. In vitro studies suggested that transfer across the placenta was minimal 12, 13, 14 and glibenclamide was undetectable in cord blood 15. Early clinical studies suggested there was no significant increase in macrosomia or neonatal hypoglycaemia with the use of glibenclamide compared to insulin use 15, 16, 17, 18, 19, 20, but these studies were limited in their power to demonstrate differences 21.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Glibenclamide has until recently been considered a safe drug to use in pregnancy. In vitro studies suggested that transfer across the placenta was minimal 12, 13, 14 and glibenclamide was undetectable in cord blood 15. Early clinical studies suggested there was no significant increase in macrosomia or neonatal hypoglycaemia with the use of glibenclamide compared to insulin use 15, 16, 17, 18, 19, 20, but these studies were limited in their power to demonstrate differences 21.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
“…In vitro studies suggested that transfer across the placenta was minimal 12, 13, 14 and glibenclamide was undetectable in cord blood 15. Early clinical studies suggested there was no significant increase in macrosomia or neonatal hypoglycaemia with the use of glibenclamide compared to insulin use 15, 16, 17, 18, 19, 20, but these studies were limited in their power to demonstrate differences 21. In a meta‐analysis (10 studies on 471 women exposed to sulfonylureas and biguanides in the first trimester), no significant difference was found in the rate of major malformations or neonatal death in the offspring of women with exposure to oral antidiabetic agents in the first trimester compared with non‐exposed women, but the meta‐analysis was limited by study heterogeneity 22.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
“…Glyburide (glibenclamide, INN) (GLY), an oral sulfonylurea hypoglycemic agent, has similar outcomes as insulin when used in the treatment of gestational diabetes mellitus (GDM) [1]. GDM is typically diagnosed in the third trimester of pregnancy and affects up to 8% of all pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%
“…GLY improves glycemic control by increasing the release of insulin from the β cells of the pancreas. When compared to treatment with exogenous insulin, GDM patients on GLY have higher compliance, similar maternal glucose control and similar infant outcomes such as macrosomia and neonatal hypoglycemia [1]. For these reasons, GLY is increasingly used as first-line therapy for GDM.…”
Section: Introductionmentioning
confidence: 99%
“…In United States, there is emerging interest for the use of sulphonylureas, especially glyburide, during pregnancy. In a randomized study comparing glyburide with insulin therapy, women treated with glyburide achieved similar degree of glycaemic control to those in the insulin group [53]. The risks of macrosomia, respiratory distress, neonatal hypoglycaemia and need for neonatal intensive care support were not different between the 2 groups.…”
Section: Oral Anti-hyperglycaemic Agentsmentioning
confidence: 91%